Evaluation of the implementation of the South African Triage System at an academic hospital in central Haiti. (July 2017) - Rouhani, Shada A.; Aaronson, Emily; Jacques, Angella; Brice, Sandy; Marsh, Regan H.
Highlights: The South African Triage System (SATS) was successful with limited formal training. Completion of clinical discriminators was less common than the numeric triage score. In this setting, SATS had low undertriage but high overtriage rates. Abstract: Background: Effective triage is an important part of high quality emergency care, yet is frequently lacking in resource-limited settings. The South African Triage Scale (SATS) is designed for these settings and consists of a numeric score (triage early warning score, TEWS) and a list of clinical signs (known as discriminators). Our objective was to evaluate the implementation of SATS at a new teaching hospital in Haiti. Methods: A random sample of emergency department charts from October 2013 were retrospectively reviewed for the completeness and accuracy of the triage form, correct calculation of the triage score, and final patient disposition. Over and under triage were calculated. Comparisons were evaluated with chi-squared analysis. Results: Of 390 charts were reviewed, 385 contained a triage form and were included in subsequent analysis. The final triage color was recorded for 68.4% of patients, clinical discriminators for 48.6%, and numeric score for 96.1%. The numeric score was calculated correctly 78.3% of the time; in 13.2% of patients a calculation error was made that would have changed triage priority. In 23% of cases, chart review identified clinical discriminators should have been circled but were not recorded. Overtriage and undertriage were 75.6% and 7.4% respectively. Conclusion: This study demonstrates that with limited structured training, SATS was widely adopted, but the clinical discriminators were used less commonly than the numeric score. This should be considered in future implementations of SATS.